Health Insurance Coverage Among Veterans Receiving Care From VA Health Care Facilities. (August 2022) - Stroupe, Kevin T.; Martinez, Rachael; Hogan, Timothy P.; Gordon, Elisa J.; Gonzalez, Beverly; Tarlov, Elizabeth; Silva, Abigail; Huo, Zhiping; Kale, Ibuola; Ippolito, Dolores; Osteen, Chad; Jordan, Neil; et al.
Reasons for acquiring insurance outside Department of Veterans Affairs (VA) health care coverage among VA enrollees are incompletely understood. To assess Veterans' decision-making and acquisition of non-VA health care insurance in the Affordable Care Act era, we used mailed questionnaires and semistructured interviews in a stratified random sample of VA enrollees <65 years in the Midwest. Of the 3, 666 survey participants, 32.1% reported non-VA insurance. Frequently reported reasons included wanting coverage for emergency situations or family members. Those without non-VA insurance cited unaffordability as the main obstacle. Analysis of the semistructured interview data revealed similar findings. In multivariable logistic regression analyses, characteristics associated with non-VA insurance included higher income (>50, 000 vs. <10, 000, odds ratio [OR] = 5.95, 95% confidence interval [CI]: 3.45–10.3, p < .001). As financial barriers exist for acquisition of non-VA insurance and hence community care, it is critically important that VA enrollees' health care needs are met through VA or community providers financed through VA.